A STAGGERED MAIZE–LEGUME INTERCROP ARRANGEMENT INFLUENCES YIELD, WEED SMOTHERING AND NUTRIENT BALANCE IN THE EASTERN HIMALAYAN REGION OF INDIA. (12th April 2016) - CHOUDHARY, V. K.; CHOUDHURY, B. U.
SUMMARY: The effects of sole and intercropping of rainfed maize ( Zea mays L.) were evaluated with soybean ( Glycine max L.) and groundnut ( Arachis hypogea L.) on crop yield, weed smothering efficiency (WSE) and nutrient (NPK) balance at Eastern Himalayan Region (EHR), India. Grain yield of maize was highest (3886 to 4110 kg ha −1 ) in the solitary system followed by maize-soybean intercrops at 1:2 rows. However, system productivity as well as production efficiency was higher by 47.3-63.3% and 39.5-58.4%, respectively in intercropping with groundnut at 1:5 rows compared to solitary maize. WSE was relatively higher to solitary soybean and was comparable to maize-groundnut intercropping at 1:5 row proportions. Similarly, NPK uptake was higher in intercropping of maize-soybean systems at 1:5 row proportions. Inclusion of legumes as intercrops in predominantly solitary rainfed maize may improve the system productivity while sustaining the nutrient availability in the vast uplands of the EHR and other similar rainfed hilly ecosystems.